Analisis Korelasi Perubahan Tutupan Vegetasi Terhadap Perubahan Suhu Udara di Kota Denpasar - ZAL, MAR’IE ABDA’U; Nuarsa, I Wayan; UTAMI, NI WAYAN FEBRIANA (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2017)
The rate of growth and development of Denpasar city increases the demand for land to supply the needs of urban facilities and infrastructure. This affected to the increase of conversion of vegetation coverage into built-up land cover. The conversion of the vegetation coverage impacts on urban environmental quality which is increase the rate of air temperature.  The purpose of this study is to examine the impact of vegetation coverage change on the air temperature change in Denpasar city in year of 2003, 2009 and 2015.  Remote sensing and regression statistic method were used in this study.  The results showed that the decrease of vegetation coverage influenced the increase of air temperature in Denpasar city. Statistically, the correlation can be projected on the equation y = 31,295-0,078x , where x and y are vegetaton coverege and air temperature respectively.  This equation shows that decresing of 1% vegetation coverege will increase 0,078 o C of air temperature. The effort to conceder in responding to the temperature rise that occurred in Denpasar is increasing the number of green open space. Based on the classification value of vegetation coverage and air temperature of Denpasar City, there are three categories of priority areas for green open space development that is high, medium and low priority. The development of green open space in each priority area can be adjusted to the characteristics of land use.